Epistemology of Islamic Law Determination in Bahsul Masail Nahdlatul Ulama: Epistemologi Penetapan Hukum Islam dalam Bahsul Masail Nahdlatul Ulama - Muhajirin, Bayu; Aziz, Muhammad (Institut Agama Islam Negeri Fattahul Muluk Papua, 2025)
Problems of Islamic law faced by Muslims in Indonesia are always growing and complex. Such conditions should encourage Islamic jurists and Islamic religious organizations in Indonesia to respond to them.The purpose of this research is to identify the construction of the ijtihad methodology of the Lembaga Bahsul Masail Nahdlatul Ulama. This research uses a qualitative method in the form of a literature study with this analytical approach. Data using various scientific literature that discusses the ijtihad method of the Nahdlatul Ulama Bahsul Masail Institute. The trilogy of Islamic epistemology (bayani, burhani, and irfan) becomes the basis of perspective in analyzing the subject matter. This study concludes that the epistemological basis in the construction of the Nahdlatul Ulama Bahtsul Masail Institute methodology tends to use the bayani and burhani integration method. The integrative method can be seen from the methodological hierarchy of determining Islamic law through the stage of the qauli method (textual method), which refers to the opinions of the four madhhab fiqh books by referring directly to existing texts. Then, the ilhaqi method (analogy method), which is a method of finding similarities between new cases and old cases that already have a legal basis in the fiqh books to be applied to the new case. Furthermore, the manhaji method (methodological method), which is applying the framework of thinking and rules in determining the law that has been compiled by the Imam of the madhhab. This research confirms that the method of determining Islamic law in the Lembaga Bahsul Masail Nahdlatul Ulama uses a method that combines the footing of authoritative fiqh literature with the intellectual logic of fiqh contextually.